2004
DOI: 10.1016/j.otc.2004.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of patients with smell and taste disorders

Abstract: Clinical assessment of the patient who has smell and taste disorders requires understanding of the etiology of the olfactory and gustatory disorders. Available clinical tests of olfactory and gustatory systems allow detecting and measuring the degree of the sensory loss, but are unable to determine the cause and give neither prognostic information nor therapeutic guidance. With physical examination, however, clinical history can help to establish the diagnosis and guide the treatment if available. A clinician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
1
17

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 44 publications
1
109
1
17
Order By: Relevance
“…Our results showed that nasal polyposis patients exhibited a general decrease in olfactory function, and this finding appears to be a confirmation of the welldocumented olfactory dysfunction in patients with sinonasal disease [2,3,11,21] . The first variable entered into our study was sex, with females having on average better results in the olfactory test, a fact consistent with previous studies [12,22] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results showed that nasal polyposis patients exhibited a general decrease in olfactory function, and this finding appears to be a confirmation of the welldocumented olfactory dysfunction in patients with sinonasal disease [2,3,11,21] . The first variable entered into our study was sex, with females having on average better results in the olfactory test, a fact consistent with previous studies [12,22] .…”
Section: Discussionsupporting
confidence: 85%
“…The development of standardized olfactory tests which are available in every-day clinical practice offered a more objective method to assess smell problems than the subjective symptom rating [11] . This study was conducted to evaluate whether CT scan findings in a group of patients with the same nasal pathology are correlated with the results of a well-investigated olfactory test [12,13] and with subjective perception of olfactory dysfunction.…”
mentioning
confidence: 99%
“…Lang et al [5] assessed taste function using whole mouth test and TST, while the other two studies [6,7] used electrogustometry. Electrogustometry is more sensitive to slight taste impairment and provides quantitative measure of taste function, but is inappropriate for evaluation of taste qualities other than sour or ''metallic'' [14]. The difference in stimulation time on electrogustometric testing (0.5 vs. 1.5 s) might also be at least partly responsible for the contrasting results between the last two studies [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…2,18,19) Some drugs may impact taste sensitivity by their direct stimulation of taste receptors, not only by altering the normal transduction process and cellular functions, but also by altering the salivary flow. [20][21][22] The reduction of saliva seems to be highly related to the decline of taste perception in the elderly because of the high prevalence of systemic disease and its treatment with drugs in such individuals.…”
Section: Epidemiolocal Evidence Supporting a Link Between Hypogeusia mentioning
confidence: 99%